2015
DOI: 10.1007/s11010-015-2509-9
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin D induces cell cycle arrest and apoptosis by inhibiting STAT3 and NF-κB signaling in doxorubicin-resistant human breast carcinoma (MCF7/ADR) cells

Abstract: Breast cancer is the most common cancer for women and is a major cause of mortality in women. Doxorubicin is a generally used chemotherapy drug for breast cancer. However, multidrug resistance of breast cancer interferes with the chemotherapy. We examined whether cucurbitacin D affects doxorubicin resistance of MCF7/ADR breast cancer cells. Cell viability was measured by MTT assay. Levels of p-STAT3, p-NF-κB, IκB, and caspases were measured by Western blot analysis. Nuclear staining of Stat3 and NF-κB was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 29 publications
4
44
1
Order By: Relevance
“…Cucurbitacin B is found in many Cucurbitaceous plant species and is one of the abundant forms of cucurbitacins22. Cucurbitacin D is one of the analogue of cucurbitacins which has shown anti-cancer activity against various types of cancer2324252627. Most of the studies have revealed anti-cancer effects of Cucurbitacin D via induction of apoptosis and suppression of constitutive activation of NF-κB and STAT3.…”
mentioning
confidence: 99%
“…Cucurbitacin B is found in many Cucurbitaceous plant species and is one of the abundant forms of cucurbitacins22. Cucurbitacin D is one of the analogue of cucurbitacins which has shown anti-cancer activity against various types of cancer2324252627. Most of the studies have revealed anti-cancer effects of Cucurbitacin D via induction of apoptosis and suppression of constitutive activation of NF-κB and STAT3.…”
mentioning
confidence: 99%
“…Stat3 activation is a predictive marker of drug resistance because it is linked to the development of doxorubicin resistance in cancer cell lines. 11,45,46 We found that cucurbitacin D decreased the levels of p-Akt and p-Stat3 in MCF7, MDA-MB-231, and SKBR3 cells. However, doxorubicin alone did not decrease p-Akt and p-Stat3 levels.…”
Section: Discussionmentioning
confidence: 73%
“…The MCF7 cell line has an induced upregulation of activated Stat3 and shows resistance to doxorubicin. [11][12][13] Signal transducers and activators of transcription (Stat) proteins are transcription factors. The Stat family is composed of Stats 1, 2, 3, 4, 5a, 5b, and 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Dox induces nuclear factor-κB (NF-κB) activation which is believed to contribute to the development of chemoresistance [56]; thus, a viable option in cancer therapy could be the inhibition of NF-κB activation to overcome the chemoresistance. Among various biological systems exploited to obtain therapeutic benefits, the ubiquitin-proteasome system has been associated with tumor cell survival [57].…”
Section: Combined Therapy With Proteasome Inhibitormentioning
confidence: 99%